German atrocities, 1914 : a history of denial - Horne, John 1949- (Yale Univ. Press, 2001)
Machine generated contents note: Part I Invasion, 1914 --Chapter 1 German invasion, part 1 -- [1] The shock of Liege -- [2] The First and Second Armies to the French frontier -- [3] The destruction of Louvain -- [4] The Third Army and Dinant -- Chapter 2 German invasion, part 2 -- [1] The battle of the Ardennes -- [2] The Germans in the Meurthe-et-Moselle -- [3] To the Marne and back: September-October 1914 -- [4] The pattern of German military violence towards civilians -- [5] Comparisons --Part II War of illusions? 'Francs-tireurs' and -- 'German atrocities', 1914 -- Chapter 3 The German army and the myth of the -- francs-tireurs, 1914 -- [1] Concepts and precedents -- [2] The myth-complex of the 'franc-tireur war' -- [3] The military situation and the franc-tireur fear -- [4] The internal dynamic of the franc-tireur fear -- Chapter 4 Memories, mentalities, and the German -- response to the 'franc-tireur war' -- [1] Memories of 1870 and the laws of war -- [2] German nationalism: externalizing the enemy within -- [3] The German way of war? Responding to the -- 'franc-tireur war' --Chapter 5 Allied opinion and German atrocities', -- August-October 1914 -- [1] Refugees, soldiers, and the Allied invasion 'lear' of 1914 -- [2] Allied narratives of victimhood -- [3] Rape, mutilation, and severed hands -- [4] Representing 'German atrocities': the role ol' the press -- [5] Memories, mentalities, and the cotlstrllicl.ioi ol'(ierlnan -- atrocities' --Part III War of words, 1914-1918: German -- atrocities and the meanings of war --Chapter 6 The battle of officia reports and the tribunal -- of world opinion -- [1] The battle of official reports: the Allied ch.argcs -- [2] German counter-attack: the 'White Book' -- [3] The Belgian riposte: the 'Grey Ilook' a(l li'ernall van -- Langenhove -- [4] Neutral witness and the tribunal ol' world opinion --Chapter 7 Communities of truth and the atrocities' -- question -- [1] Socialists -- [2] Catholics -- [3] Intellectuals --Chapter 8 Wartime culture and enemy atrocities -- [1] War cultures and the unreconcilable ellemly -- [2] War cultures and national martyrdom -- [3] Sustaining the meaning of 1914 -- Part IV The impossible consensus: German -- atrocities and memories of war from -- 1919 --Chapter 9 The moral reckoning: Versailles and the war -- crimes trials -- [1] Versailles -- [2] The Leipzig war crimes trials, 1921 -- [3] War cultures after the war -- Chapter 10 German atrocities and the politics of memory -- [1] The pacifist turn: German atrocities as Allied propaganda -- [2] Locarno and the politics of memory -- [3] The Second World War and after --Conclusion and perspectives -- Appendices -- [1] German atrocities in 1914: incidents with ten or more -- civilians killed -- [2] Hague Convention (IV) Respecting the Laws and Customs -- of War on Land (1907) -- [3] The Treaty of Versailles, Articles 227-230 -- [4] Allied demands for the extradition of enemy war -- criminals, 1920